2016
DOI: 10.1007/s11606-015-3571-4
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Receipt of Guideline-Concordant Long-Term Opioid Therapy and All-Cause Mortality

Abstract: PURPOSE:For patients receiving long-term opioid therapy (LtOT), the impact of guideline-concordant care on important clinical outcomes-notably mortality-is largely unknown, even among patients with a high comorbidity and mortality burden (e.g., HIV-infected patients). Our objective was to determine the association between receipt of guideline-concordant LtOT and 1-year all-cause mortality. METHODS: Among HIV-infected and uninfected patients initiating LtOT between 2000 and 2010 through the Department of Vetera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 59 publications
6
34
0
Order By: Relevance
“…Because of the varied risks associated with opioid exposure Saunders et al, 2010;Solomon et al, 2010;Roy et al, 2011;Li et al, 2013;Veldhuizen & Callaghan, 2014) and the inherent challenges in accurately determining underlying cause of death, particularly for overdose deaths (Myers & Farquhar, 1998;Betz et al, 2008;Goldberger et al, 2013;Warner et al, 2013;Huguet et al, 2014;Slavova et al, 2015), we chose as our primary outcome allcause mortality. We found that patients who received psychotherapeutic co-interventions (i.e., mental health services) had lower mortality, while those receiving benzodiazepine concurrent with opioids had higher mortality (Gaither et al, 2016). Notably, we found that patients with an untreated substance use disorder had a mortality rate more than twice that of those who were engaged in treatment for this disorder (Gaither et al, 2016).…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…Because of the varied risks associated with opioid exposure Saunders et al, 2010;Solomon et al, 2010;Roy et al, 2011;Li et al, 2013;Veldhuizen & Callaghan, 2014) and the inherent challenges in accurately determining underlying cause of death, particularly for overdose deaths (Myers & Farquhar, 1998;Betz et al, 2008;Goldberger et al, 2013;Warner et al, 2013;Huguet et al, 2014;Slavova et al, 2015), we chose as our primary outcome allcause mortality. We found that patients who received psychotherapeutic co-interventions (i.e., mental health services) had lower mortality, while those receiving benzodiazepine concurrent with opioids had higher mortality (Gaither et al, 2016). Notably, we found that patients with an untreated substance use disorder had a mortality rate more than twice that of those who were engaged in treatment for this disorder (Gaither et al, 2016).…”
Section: Introductionmentioning
confidence: 68%
“…We found that patients who received psychotherapeutic co-interventions (i.e., mental health services) had lower mortality, while those receiving benzodiazepine concurrent with opioids had higher mortality (Gaither et al, 2016). Notably, we found that patients with an untreated substance use disorder had a mortality rate more than twice that of those who were engaged in treatment for this disorder (Gaither et al, 2016). It was this finding that prompted the current study, in which we sought to better understand how the presence of a substance use disorder moderated the outcome of all-cause mortality for the remaining indicators (i.e., psychotherapeutic co-interventions and benzodiazepine coprescribing).…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…T he article by Gaither et al 1 in this issue of JGIM is an important study. First, and most importantly, it properly concludes that initiating long-acting opioids in patients at increased risk for an overdose event or other serious harms related to co-prescription of benzodiazepines or in those with untreated substance use disorder is not a good idea.…”
mentioning
confidence: 99%